2016
DOI: 10.1177/0040517516654104
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and water vapor transport properties of selected lofty nonwoven products

Abstract: The mechanism of dry heat flow through lofty nonwoven structures (i.e. thermal resistance) as occurs in quilts has been established. By contrast, there is a scarcity of published information on the water vapor transport properties. This work explores the thermal and water vapor transport properties of a number of different quilt samples with a focus on identifying fiber type effects. Both commercial product and matched laboratory samples were examined. Steady-state thermal resistance and water vapor resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This was surprising as the TL was also the thickest material, yet it had the greatest MTHL. 31 Although the TL consists of a thick, multi-layer construction, the MB had a higher evaporative resistance ( R et ) on the garment level, which contributed to its overall lower heat loss within the context of this particular study’s predicted test conditions and specific garment materials.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This was surprising as the TL was also the thickest material, yet it had the greatest MTHL. 31 Although the TL consists of a thick, multi-layer construction, the MB had a higher evaporative resistance ( R et ) on the garment level, which contributed to its overall lower heat loss within the context of this particular study’s predicted test conditions and specific garment materials.…”
Section: Discussionmentioning
confidence: 84%
“…This contradicts previous literature that found fabric thickness to be the primary predictor of thermal insulation; however, the previous study assessed fabric-level test methods only. 31 Previous research also found garments with higher permeability to have lower thermal resistance through natural convection. 32 In this study, however, opposite results were found as the thick TL had the greatest air permeability and overall MTHL but did not have the lowest thermal resistance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…41 Fiber effects on the water vapor transport properties of lofty structures (comforter fillings) have been previously studied. 7,31 Naylor et al 7 concluded that, under steady-state conditions, water vapor resistance is determined by thickness, independent from the fiber type, whereas shell fabric plays a minor role. In this study, the thicknesses of tested pillows were comparable (see Table 10, column h p0 ) and the measured R e values ( Table 7) are not proportional to pillow thickness.…”
Section: Microclimate Of Pillowsmentioning
confidence: 99%
“…The importance of moisture management in bedding material for the improved quality of sleep was also emphasized in a sleep study by the Joanneum Research Institute for Non-Invasive Diagnosis, 6 in which physiological and psychometric data derived from the participating subjects' heart functions during night sleep were monitored. A study conducted by Naylor et al 7 on lofty nonwoven structures from wool and polyester (PET) demonstrated that the heat resistance and water vapor permeability of a textile material are determined solely by its thickness and air content (voids) in steadystate conditions, and not by fiber type. Fiber type has a significant impact on thermal and water vapor transport properties under transient conditions.…”
mentioning
confidence: 99%